2018
DOI: 10.1016/j.ajo.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function Metrics in Early and Intermediate Dry Age-related Macular Degeneration for Use as Clinical Trial Endpoints

Abstract: Purpose To evaluate and quantify visual function metrics to be used as predictors of AMD progression and visual acuity (VA) loss in patients with early and intermediate AMD. Design Baseline data of observational, cross-sectional, prospective study. Methods 101 patients were enrolled at Duke Eye Center: 80 patients with AMD age-related eye disease study (AREDS) stage 2 (N=33) and stage 3 (N=47) and 21 age-matched, normal controls. A dilated retinal examination, macular pigment optical density measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 39 publications
8
112
0
Order By: Relevance
“…By studying mesopic vision to include both rod and cone responses, it becomes clear that rods play a role in colour vision, and not just light adaptation. The differing characteristics of rods vs cones for light level, wavelength, retinal eccentricity, and temporal and spatial aspects of vision result in functional differences between controls and patients with AMD for scotopic, mesopic, and photopic mechanisms, along with adaptation, colour contrast, acuity, etc …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By studying mesopic vision to include both rod and cone responses, it becomes clear that rods play a role in colour vision, and not just light adaptation. The differing characteristics of rods vs cones for light level, wavelength, retinal eccentricity, and temporal and spatial aspects of vision result in functional differences between controls and patients with AMD for scotopic, mesopic, and photopic mechanisms, along with adaptation, colour contrast, acuity, etc …”
Section: Discussionmentioning
confidence: 99%
“…The differing characteristics of rods vs cones for light level, wavelength, retinal eccentricity, and temporal and spatial aspects of vision result in functional differences between controls and patients with AMD for scotopic, mesopic, and photopic mechanisms, along with adaptation, colour contrast, acuity, etc. 95,96 In addition to retinal remodelling that occurs with loss of neurons, 84 there is the potential for binocular summation or inhibition, with differences due to binocular disparity, spatial frequency, and eccentricity. 97 In patients with geographic atrophy and AMD, potential vision is not accurately assessed by limiting measurements only to initial ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, the wide spectrum of the kidney involvement in SLE patients needs a larger population to better explore the potential correlation between renal function and ophthalmological findings. HCQ is cleared to a large degree by the kidney, and as such renal disease may increase the circulating level of the drug and the risk of toxicity [28, 29]. Therefore, patients with renal disease might have unpredictably high blood drug levels and a higher risk of toxicity, although there are no specific data to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…The same group later reported that baseline LLD was not correlated with 12-month changes in VA measures or microperimetric sensitivity, although changes in VA were minimal over this period. 15 Cocce et al 3 found that LLD was significantly different between early and intermediate AMD patients, but only on computerized assessment. Although the utility of LLD in the classification of AMD remains unclear, it is likely still useful as a practical measure of patient functionality.…”
Section: Low-luminance or Mesopic Conditions Represent A Transitionmentioning
confidence: 99%
“…Visual acuity (VA), the most commonly used measure of visual function, is often unaffected in early and intermediate stage disease. 3 To better stratify disease severity and risk of progression to more advanced disease, there is a need to identify additional markers for AMD progression and to understand the relationships between these markers.…”
Section: Introductionmentioning
confidence: 99%